The finance of international business - Kettell, Brian (London : Graham & Trotman, 1979)
This book considers how the financial executives should handle currency fluctuations and exchange controls; how best use can be made of capital and money markets, and how differing economic conditions in countries should be taken into account in arriving at a reasonable financial strategy for firm.
Includes index.
Bibliography: p. 261-267.
usc 16/08/18
Loans
Keywords: International business enterprises; International finance; Corporations, Finance